URBAN REGENERATION PROCESS - THE CASE OF GENOA, AN EXAMPLE OF INTEGRATED URBAN DEVELOPMENT APPROACH - Rossana Galdini (European Regional Science Association (ERSA), 2005)
This paper analyzes the process of Urban Regeneration in Europe and examines the factors influencing this process as well as its implementation. Foundamental changes in the economy, technology, demography and politics are reshaping the environment for cities in Europe. These changes have induced a logic of competion in a dynamic and complex context. In the attempt to become and remain an attractive place for inhabitants, city users, businessmen and visitors, cities invent their own strategies, discovering that the policies of local governments need to be more marked-oriented with an eye to the city's weaknesses and strenghts. Many historic cities in recent decades experienced redevelopment for new "postindustrial uses” often related to culture, tourism, technology. Such uses may offer the potential for creating more sustainable and liveable cities. Especially in old industrial areas, new politics, strategies and funds have been used for re-utilization of old industrial sites. Clear examples for this is Italian case studies like Genoa. In Genoa a programme for restructuring the old harbour areas, the waterfront and the historic centre has been set up. Genoa approaches functional specialisation as a more general element in its strategy for increasing economic competitiveness. The development of transport systems, services, infrastructures, promises considerable renovation of the urban functions with a significant growth in the economy linked to cultural activities and tourism. Regeneration programmes for de-industrialised areas have promoted the location and relocation of business investments as well as actions to improve a productive diversification. At present Genoa after a deep crisis, has regained a new identity and its role in the Italian economic and social system. This paper integrates three issues. First it describes some of the main features of pattern of urban development and the increase of competition, setting the scene for a more strategic action. Second analyzes the case study Genoa, an example of integrated urban development approach. Third attention is drawn on the way in which cities "create” their own image management, using actions that shown and reveal hidden resources.
Keywords: 330